The Close AGN Reference Survey (CARS): no obvious signature of AGN feedback on star formation, but subtle trends - Smirnova-Pinchukova, Irina; Husemann, Bernd; Davis, T. A.; Smith, C. M. A.; Singha, M.; Tremblay, G. R.; Klessen, Ralf S.; Powell, M.; Connor, T.; Baum, S. A.; Combes, F.; Croom, S. M.; et al. (Astronomy and astrophysics, 2022)
Active galactic nuclei (AGN) are thought to be responsible for the suppression of star formation in massive ∼1010 M⊙ galaxies. While this process is a key feature in numerical simulations of galaxy formation, it has not been unambiguously confirmed in observational studies yet.Aims. The characterization of the star formation rate (SFR) in AGN host galaxies is challenging as AGN light contaminates most SFR tracers. Furthermore, the various SFR tracers are sensitive to different timescales of star formation from approximately a few to 100 Myr. We aim to obtain and compare SFR estimates from different tracers for AGN host galaxies in the Close AGN Reference Survey (CARS) to provide new observational insights into the recent SFR history of those systems.Methods. We constructed integrated panchromatic spectral energy distributions to measure the far infrared (FIR) luminosity as a tracer for the recent (< 100 Myr) SFR. In addition we used the integral-field unit observation of the CARS targets to employ the Hα luminosity decontaminated by AGN excitation as a proxy for the current (< 5 Myr) SFR.Results. We find that significant differences in specific SFR of the AGN host galaxies as compared with the larger galaxy population disappear once cold gas mass, in addition to stellar mass, is used to predict the SFR for a specific AGN host. Only a tentative trend with the inclination of the host galaxy remains, such that SFR appears slightly lower than expected when the galaxies of unobscured AGN appear more edge-on along our line-of-sight, particular for dust-insensitive FIR-based SFRs. We identify individual galaxies with a significant difference in their SFR which can be related to a recent enhancement or decline in their SFR history that might be related to various processes including interactions, gas consumption, outflows, and AGN feedback.Conclusions. AGN can be present in various stages of galaxy evolution which makes it difficult to relate the SFR solely to the impact of the AGN. Our study shows that stellar mass alone is an insufficient parameter to estimate the expected SFR of an AGN host galaxy compared to the underlying non-AGN galaxy population. We do not find any strong evidence for a global positive or negative AGN feedback in the CARS sample. However, there is tentative evidence that (1) the relative orientation of the AGN engine with respect to the host galaxies might alter the efficiency of AGN feedback and that (2) the recent SFH is an additional tool to identify rapid changes in galaxy growth driven by the AGN or other processes.
Gesehen am 20.04.2022